Processo de purificação do biogás na biorrefinaria de biometano da Itaipu: um estudo de caso - Fredo, Fábio Augusto Minetto (2019)
Investments in new energy sources such as research and development to improve existing sources depend on a number of factors such as demands for energy, electrical, thermal or mechanical, development of renewable energy in place of fossil fuels as well as increasing animal production for consumption. The standardization of management and the need for waste disposal, made the production and use of biogas significantly increased as a source of energy. The ITAIPU biomethane biorefinery, which works by the Water Scrubbing process, where the working pressure (the higher the pressure, the higher the solubility) and the water temperature (the lower the higher the solubility), together with the flow rate. of water at the time of gas "flushing" form the main features of a 'WS' process. This work aimed to study the variables around the solubility of CO2 in water. In this study, it was found that there is no efficient temperature control in the process in question, directly influenced by the local environmental issues, the pressure is kept constant by the working pressure of the compressor and the towers and the flow was identified as much higher than necessary if the variables were better controlled. Another aspect analyzed was the addition of a water additive, Triethanolamine, which gave a higher absorption power to the solution.